Avaliação das alterações endoscópicas e histológicas de pacientes que se infectaram por COVID-19: estudo retrospectivo - Azôr, Fernanda Oliveira (2024)
INTRODUCTION: The emergence and spread of SARS-CoV-2 since December 2019 has brought major challenges to global public health. Patients infected with COVID-19 may also experience gastrointestinal symptoms with sequelae that include: loss of appetite, nausea, acid reflux, and diarrhea - common in patients even three months after infection. The endoscopic examination is abnormal in most cases, with great heterogeneity in the findings. OBJECTIVE: To evaluate endoscopic and histological changes in patients with a previous history of COVID-19 infection. MATERIAL AND METHODS: The medical records and records of 102 patients were analyzed with information on the variables: gender, age, height, BMI, the reason for performing the upper digestive endoscopy (EDA) examination, time in weeks elapsed between the diagnosis of COVID-19 and the performance of EDA, comorbidities, medication use and endoscopic and histopathological findings. RESULTS: The average time elapsed since the diagnosis of COVID-19 and the endoscopy was 28.09 +- 14.59 weeks. Around 41% of patients had some degree of obesity. The main reasons for performing EDA were gastroesophageal reflux (5.88%), abdominal pain (25%), epigastric pain (10.78%), preoperative bariatric surgery (10.78%), and routine (30 .39%). Regarding the use of Ivermectin, around 46% of those interviewed chose to use it. Regarding the use of Hydroxychloroquine, only five patients used it during the infection. In total, 27.44% of endoscopies showed some degree of erosive esophagitis; 67.65% had an endoscopically normal gastric body and 49.02% had enanthematous gastritis of the gastric antrum. Duodenitis was less frequent, being described in less than 10% of the exams performed. Regarding the use of medications, patients who used Hydroxychloroquine during COVID-19 treatment were likely to present 14.73 times more endoscopic findings of the gastric body than those who did not use it. With the use of Amoxicillin, there was a 19.6 times higher probability of esophageal changes. Patients with diabetes mellitus were 5.6 times more likely to have esophageal changes and 7.57 times more likely to have duodenal changes when compared to healthy individuals. CONCLUSION: Statistical data demonstrated a greater probability of endoscopic findings in patients with comorbidities and confirmed antibiotic use during the infection period. Several factors may justify the results found, such as the significant sample of patients with obesity. Due to the long average interval between infection and the EDA being carried out; further studies are needed to assess whether possible late gastrointestinal symptoms and endoscopic changes can be justified by previous exposure to the virus.